The association between interhospital transfer and sepsis guideline adherence among rural emergency department patients - Cole Wymore; Eliezer Santos León; Priyanka Vakkalanka; Uche Okoro; Karisa K. Harland; Brian M. Fuller; Kalyn Campbell; Morgan B. Swanson; Brett Faine; Anne Zepeski; Edith A. Parker; Luke J. Mack; et al. (PLoS ONE, 2026)
Introduction The objective of this study was to assess whether interhospital transfer delays completion of the Surviving Sepsis Campaign (SSC) 3-hour bundle among rural sepsis patients. Methods We conducted a multicenter (n = 23) cohort study among adult rural sepsis patients in an ED-based telemedicine network between August 2016 and June 2019. The primary exposure was interhospital transfer and the primary outcome was completion of the SSC 3-hour bundle. Secondary outcomes included SSC component adherence, ED length-of-stay, and in-hospital mortality. We used a Cox proportional hazards model to evaluate time to bundle completion by transfer status, generalized linear models for dichotomous outcomes, and linear and quantile regression for ED length-of-stay. Results A total of 1,191 patients were treated in participating hospitals, with 359 (30%) undergoing interhospital transfer. SSC bundle adherence was similar in both groups (difference 2.2%; 95% confidence interval [CI]: – 2.2, 6.5%). Among eligible patients, transfer was associated with a longer ED length-of-stay (3.1 hours vs 2.6 hours; difference 0.6 hours; 95%CI: 0.4, 0.7).